1988
DOI: 10.1038/jcbfm.1988.3
|View full text |Cite
|
Sign up to set email alerts
|

Flow Thresholds for Cerebral Energy Disturbance and Na+ Pump Failure as Studied by in vivo 31P and 23Na Nuclear Magnetic Resonance Spectroscopy

Abstract: Summary:The relationships among CBF, cerebral en ergy metabolism, Na + pump activity, and electrocortico grams (ECoG) following graded hypotension were studied in 48 gerbils. Energy metabolism and Na+ pump activity were estimated by in vivo 31p and 23Na nuclear magnetic resonance (NMR) spectroscopy, and CBF was determined by [14C]iodoantipyrine methods at the end of the experiments. The CBF measured in normotensive an imals was 0.51 ± 0.07 ml/g brain/min. Following graded hypotension, no 31p spectral change wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…2), consistent with a finding in gerbil by Naritomi et al (1988), before there was an appreciable decline in the ATP. Thus, in contrast to the previous indirect conclusion of Crockard et al (1987), it seems that EEG activity does not fail be cause energy in the form of ATP is not available.…”
Section: Resultssupporting
confidence: 90%
“…2), consistent with a finding in gerbil by Naritomi et al (1988), before there was an appreciable decline in the ATP. Thus, in contrast to the previous indirect conclusion of Crockard et al (1987), it seems that EEG activity does not fail be cause energy in the form of ATP is not available.…”
Section: Resultssupporting
confidence: 90%
“…LCBF/energy metabolism thresholds cannot be assigned precisely because of the large variability of our data. However, our results are in agreement with those recently reported by Crockard et al (1987) and Naritomi et al (1988). Crockard's group combined measurements of LCBF with H 2 clearance in brain regions of gerbils subjected to unilateral or bilateral carotid occlu sion, with measurements of phosphorus metabo lites, intracellular pH, and lactate made by 31p and lH NMR spectroscopy .…”
Section: Matching Flow and Metabolic Parameterssupporting
confidence: 93%
“…Their study revealed a threshold effect in the metabolism of cerebral tissue with CBF under 20 mllmin/100 g . Naritomi et al (1988) com bined autoradiographic measurements of LCBF with 31p and 2 3Na NMR; they found that PCr and ATP began to decrease at a CBF level of 18-23 and 12-14 mllmin/100 g, respectively.…”
Section: Matching Flow and Metabolic Parametersmentioning
confidence: 99%
“…min-' -100 g-' was associated with failure to maintain control levels of cerebral high energy metabolites. This CBF is higher than the critical flow threshold for energy failure in adult animals of other species such as gerbils (13,14). When expressed as a relative reduction in CBF, energy failure in piglets occurs at similar flow decrements as in adult rats (10) and gerbils (14).…”
Section: Discussionmentioning
confidence: 95%
“…Recently combined CBF and 31P NMR measurements have established that the flow threshold for energy failure is in the range of 12-20 ml . min-' -100 g-I in adult gerbils ( 13,14).…”
mentioning
confidence: 99%